2012
DOI: 10.5194/aab-55-272-2012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a high-fibre diet on the feeding behaviour of fattening pigs

Abstract: The natural behavioural repertoire of the pig includes extensive foraging behaviour and long feeding times. Customary feed for growing pigs does not meet these requirements, resulting in unsatisfied feeding motivation. This may lead to behavioural disorders and reduces animal welfare. Studies on sows showed that by enhancing crude fibre content in the feed, satiety can be improved and the feeding motivation reduced. In growing pigs, however, studies are lacking, although abnormal behaviours are widespread. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
4
12
2
Order By: Relevance
“…reported by Hyun et al (1997), but in agreement with the values (31.3 -42.4 g min -1 ) reported by Quiniou et al (2000). A study by Kallabis and Kaufmann (2012) in growing pigs using standard diet, and two diets with inclusion of 6 % and 9% of lingo-cellulose fiber, showed longer eating time in pigs fed on fibrous diet than those fed standard diet. They conclude that the reason for longer eating time at 6 and 9 % was the fiber content which takes longer time to chew.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…reported by Hyun et al (1997), but in agreement with the values (31.3 -42.4 g min -1 ) reported by Quiniou et al (2000). A study by Kallabis and Kaufmann (2012) in growing pigs using standard diet, and two diets with inclusion of 6 % and 9% of lingo-cellulose fiber, showed longer eating time in pigs fed on fibrous diet than those fed standard diet. They conclude that the reason for longer eating time at 6 and 9 % was the fiber content which takes longer time to chew.…”
Section: Discussionsupporting
confidence: 89%
“…However, in the current study pigs fed on the standard diet containing low fiber showed longer eating time than different inclusion levels of LC, which contains higher fiber content. This contradicts with the previous studies (Quiniou et al 2000;Holt et al, 2006;Kallabis and Kaufmann, 2012). In the current study, the reason for pigs to show shorter eating time and higher eating rate min -1 in the LC could be because the pigs liked the LC.…”
Section: Discussioncontrasting
confidence: 72%
“…Soft and liquid faeces can more easily attach to the hindquarters of the pigs, which may stimulate increased levels of exploration from other pen mates. Moreover, Kallabis and Kaufmann [ 22 ] reported that pigs fed with a more fibrous diet tended to have longer feeding bouts. In the context of the current experiment, where pigs were housed on slatted floors with limited environmental enrichment and a single-spaced feeder (which are known risk factors for tail biting [ 32 ]), longer feeding bouts might have increased the likelihood of tail biting incidence.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the authors suggested that provision of a fibre source with high bulkiness could reduce oral manipulation behaviours immediately post-feeding, and highly fermentable fibre could further reduce activity levels by prolonging satiety. In growing pigs, Kallabis and Kaufmann [ 22 ] found that fattening pigs fed higher quantities of dietary fibre tended to have fewer meals per day and a lower daily feed intake but spent more time feeding and ate more slowly. Although these authors recognised the effect of high dietary fibre on improving satiety and inferred a likely reduction in oral manipulative behaviours, evidence for this is still lacking in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these overall biological factors that control appetite and satiety, little is known about the molecular connections between FE and feeding behaviour traits and its genetic and phenotypic correlations. In fact, both groups of traits are influenced by environmental and genetic factors (Kallabis and Kaufmann 2012 ; Maselyne et al 2015 ; Shirali et al 2015 ). Specifically, Fernández et al ( 2011 ) provided evidence for the occurrence of pig breed-specific feeding strategies substantiating the influence of genetics on these traits.…”
Section: Introductionmentioning
confidence: 99%